Environmental predictors of decapod species richness and turnover along an extensive Australian continental margin (13–35° S). (5th March 2013) - McCallum, Anna W.; Poore, Gary C.B.; Williams, Alan; Althaus, Franziska; O'Hara, Tim
Abstract The use of environmental data in biogeographic studies of the deep sea is providing greater insight into the processes underlying large‐scale patterns of diversity. Recent surveys of Australia's western continental margin (~100–1100 m) provide systematic sampling of invertebrate megafauna along a gradient of 22° of latitude (13–35° S). Diversity patterns of decapod crustaceans were examined and we investigated the relative importance of environmental and spatial predictor variables on both species richness (alpha diversity) and species turnover. Distance‐based linear models (DistLM) indicated a suite of variables were important in predicting species turnover, of which temperature and oxygen were the most influential. These reflected the oceanographic features that dominate distinct depth bathomes along the slope. The numbers of species within samples were highly variable; a small but significant increase in diversity towards the tropics was evident. Replicated sampling along the margin at ~100 m and ~400 m provided an opportunity to compare latitudinal patterns of diversity at different depths. On the shallow upper slope (~400 m) temperature was disassociated from latitude and the latter proved to be the best predictor of sample species richness. The predictive power of latitude over other variables indicates that proximity to the highly diverse Indo‐West Pacific (IWP) may be important, especially considering that almost 40% of species in this study had a wide IWP distribution. In the management of Australia's marine environments, geomorphic surrogates have been emphasised when defining areas for protection. We found sea‐floor characteristics were relatively less important in predicting richness or community composition.